Young women in technical professional education: Motivations, challenges and future projects - Quirino , Rachel; Gouvea , Antônia do Socorro Pinheiro; Soares , Fábio da Silveira; Soares , Luciana Aparecida Cunha; Silva , Rita de Cássia Aguiar e Souza; Grilo , Tamyris Ferreira da Silva Bianchi (Seven Editora, 2023)
This article addresses the perspectives of three students from the Technical Courses in Buildings, Mechanics and Informatics of an institution of the Federal Network of Professional and Technological Education. Due to their specificities and because they are mostly male careers, theories of gender in EFA and the sexual division of labor supported the critical analysis of the discourses of these young women. The New High School and the National Common Curriculum Base (BNCC) advocate the development of the Life Project at School, aiming, among other functions, to guide the choice of "training itineraries" and favor the personalization of student learning. In the case of Secondary Technical Education (EPTNM) in the integrated modality, students must attend the training itinerary of the general disciplines of the BNCC (Portuguese and Mathematics), together with some other chosen itinerary, compulsorily associated with Technical and Professional Training. However, in addition to fulfilling a legal obligation, knowing the real life projects of young people from EPTNM becomes essential for understanding their motivations, experiences and expectations, in relation to their professional training, the world of work and the continuity of studies. Thus, the results obtained are expected to raise reflections on the relevance of EFA in the lives of young people, taking into account the gender difference, and to promote the debate on public policies for the access and permanence of young people in technical courses. DOI:https://doi.org/10.56238/ptoketheeducati-076